Characteristics of Early Flame Development in a Direct-Injection Spark-Ignition CNG Engine Fitted with a Variable Swirl Control Valve - Abd Rashid, Abd Aziz; Anbese, Yohannes Tamirat; Hagos, F. Y.; Heikal, Morgan R.; Firmansyah, F. (MDPI AG, 2017)
An experimental study was conducted to investigate the effect of the structure of the induction flow on the characteristics of early flames in a lean-stratified and lean-homogeneous charge combustion of compressed natural gas (CNG) fuel in a direct injection (DI) engine at different engine speeds. The engine speed was varied at 1500 rpm, 1800 rpm and 2100 rpm, and the ignition timing was set at a 38.5° crank angle (CA) after top dead center (TDC) for all conditions. The engine was operated in a partial-load mode and a homogeneous air/fuel charge was achieved by injecting the fuel early (before the intake valve closure), while late injection during the compression stroke was used to produce a stratified charge. Different induction flow structures were obtained by adjusting the swirl control valves (SCV). Using an endoscopic intensified CCD (ICCD) camera, flame images were captured and analyzed. Code was developed to analyze the level of distortion of the flame and its wrinkledness, displacement and position relative to the spark center, as well as the flame growth rate. The results showed a higher flame growth rate with the flame kernel in the homogeneous charge, compared to the stratified combustion case. In the stratified charge combustion scenario, the 10° SCV closure (medium-tumble) resulted in a higher early flame growth rate, whereas a homogeneous charge combustion (characterized by strong swirl) resulted in the highest rate of flame growth.